2021
DOI: 10.1063/5.0058382
|View full text |Cite
|
Sign up to set email alerts
|

Determination of kinetic properties in unimolecular dissociation of complex systems from graph theory based analysis of an ensemble of reactive trajectories

Abstract: In this paper we report how graph-theory can be used to analyze an ensemble of independent molecular trajectories which can react during the simulation time-length and obtain structural and kinetic information. The method is totally general and here is applied to the prototypical case of gas phase fragmentation of protonated cyclo-di-glycine. The methodology allows to analyze the whole set of trajectories in an automatic computer-based way without the need of visual inspection, but getting all the needed infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 82 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…From the ensemble of trajectories and associated reaction times it is thus possible to reconstruct the number of trajectories which are in the reactant state at each time frame. If the resulting curve follows a single exponential decay (as it was generally observed in previous studies 18,20,21,[57][58][59] ) then we can directly obtain τ and thus k.…”
Section: Rate Constants From Direct Dynamics Simulationsmentioning
confidence: 94%
See 1 more Smart Citation
“…From the ensemble of trajectories and associated reaction times it is thus possible to reconstruct the number of trajectories which are in the reactant state at each time frame. If the resulting curve follows a single exponential decay (as it was generally observed in previous studies 18,20,21,[57][58][59] ) then we can directly obtain τ and thus k.…”
Section: Rate Constants From Direct Dynamics Simulationsmentioning
confidence: 94%
“…Note that it was recently shown that the rate constant obtained in such a way converges more rapidly with the number of trajectories compared to those obtained by the flux approach. 59 Each trajectory is considered to be converted to products when a given threshold distance is passed. Trajectories are then immediately stopped, so that they don't allow for recrossing, as in the main assumption of transition state theory.…”
Section: Rate Constants From Direct Dynamics Simulationsmentioning
confidence: 99%
“…Protonated cyclic dipeptides have been the subject of several studies as possible intermediates in the fragmentation of peptides. A comparison between collision-induced dissociation (CID) experiments and chemical dynamics simulations showed that the fragmentation processes of the amide CO protonated systems do not depend much on chirality, in contrast to those that are protonated on the side chain of a basic residue. Protonation modifies the balance between the different conformers of biomolecules . For cyclic dipeptides based on Tyr, Phe, or Pro residues, the proton is located on the amide CO and does not influence its conformation much.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, protonation of cyclic dipeptides usually happens on the amide CO, which results in the limited effect of chirality on their collision-induced dissociation (CID) efficiency. 45–47 Histidine-containing peptides stand out by the basic nature of the His residue, which is protonated on the imidazole ring. 48 This peculiar protonation site makes histidine very sensitive to solvation.…”
Section: Introductionmentioning
confidence: 99%